An Analysis of Herzberg’s Two-Factor Theory in Relation to the Da'wah Motivation of Mosque Youth Communities in the Greater Jakarta Area - Keisha Natania; Nasichah N; Muliafika Safinatunnajah; Ilham Khalid Faqih (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the spirit of da’wah among Mosque Youth communities in the Greater Jakarta area (Jabodetabek), namely: Masjid Jami Al Ikhlas, Masjid Baiturrahman, Masjid Al-Makmur, Masjid Jami’ An-Nur, and Masjid Al-Jami’ah, using Herzberg’s Two-Factor Motivation Theory as the theoretical framework. The focus of this research is to understand the factors that influence youths’ enthusiasm for da’wah, both intrinsic factors (motivators) such as a sense of responsibility, recognition, and spiritual meaning, and extrinsic factors (hygiene) such as the organizational environment, peer support, and mosque facilities. This study employs a qualitative approach with in-depth interviews and participatory observation of members of mosque youth communities in Jabodetabek, specifically at Masjid Jami Al Ikhlas, Masjid Baiturrahman, Masjid Al-Makmur, Masjid Jami’ An-Nur, and Masjid Al-Jami’ah. The findings indicate that the spirit of da’wah emerges when youths feel appreciated, have real roles in mosque activities, and receive positive social support. Conversely, a lack of support from the surrounding environment and inadequate da’wah facilities can reduce motivation. These findings confirm that the application of Herzberg’s Theory can help to understand and enhance the spirit of da’wah among Mosque Youth.